2011
DOI: 10.5402/2011/897908
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Younger Age, Autoimmunity, Cardiometabolic Risk, Oxidative Stress, HAART, and Ischemic Stroke in Africans with HIV/AIDS

Abstract: Background and Purpose. It now appears clear that both HIV/AIDS and antiretroviral therapy (HAART) use are associated with higher risk of cardiovascular disease such as stroke. In this study, we evaluated the prevalence, the risk factors, and the cardiometabolic comorbidities of stroke in HIV/AIDS Central African patients. Methods. This hospital-based cross-sectional study collected clinical, laboratory, and imaging data of black Central African heterosexual, intravenous drug nonuser, and HIV/AIDS patients. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…Our findings have several clinical and public health implications. As seen in other studies in Africa [27,29,49], PLHIV are younger and facing the additional burden of non-communicable diseases. There is an urgent need to implement CVD prevention and management strategies in HIV-infected patients.…”
Section: Characteristicsmentioning
confidence: 56%
“…Our findings have several clinical and public health implications. As seen in other studies in Africa [27,29,49], PLHIV are younger and facing the additional burden of non-communicable diseases. There is an urgent need to implement CVD prevention and management strategies in HIV-infected patients.…”
Section: Characteristicsmentioning
confidence: 56%
“…The rates of the disease which were considerably lower, are now rapidly increasing, even doubling in regions such as rural South Africa [4][5] . The reasons for the high burden of stroke are linked to the high rates of chronic hypertension, type 2 diabetes mellitus (T2DM), excessive alcohol intake, smoking, insufficient fruit and vegetable consumption [6][7][8] , sickle cell disease, HIV infection and even antiretroviral drugs 9 . Also, ischemic stroke is more suffered than hemorrhagic stroke 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…This concern was validated by several reports; the French Hospital Database on HIV found that patients who had been treated with protease inhibitor for 18 months or more had twice the risk of myocardial infarction that was seen among patients with less drug exposure [3]. A cross-sectional study carried out on HIV-infected patients had shown that stroke in patients with HIV/AIDS was not associated with opportunistic infections and tumors, and early assessment of the vascular status was recommended [4]. We are presenting the case of HIV-infected young patient with acute stroke to discuss the risk factors of cardiovascular events in patients with HIV infection on ART as stroke is a rising cause of disability in HIV and AIDS populations.…”
Section: Introductionmentioning
confidence: 99%